The Stability, Sustained Release and Cellular Antioxidant Activity of Curcumin Nanoliposomes - Chen, Xing (Molecules, 2015)
Curcumin is a multifunctional and natural agent considered to be pharmacologically safe. However, its application in the food and medical industry is greatly limited by its poor water solubility, physicochemical instability and inadequate bioavailability. Nanoliposome encapsulation could significantly enhance the solubility and stability of curcumin. Curcumin nanoliposomes exhibited good physicochemical properties (entrapment efficiency = 57.1, particle size = 68.1 nm, polydispersity index = 0.246, and zeta potential = −3.16 mV). Compared with free curcumin, curcumin nanoliposomes exhibited good stability against alkaline pH and metal ions as well as good storage stability at 4 °C. Curcumin nanoliposomes also showed good sustained release properties. Compared with free curcumin, curcumin nanoliposomes presented an equal cellular antioxidant activity, which is mainly attributed to its lower cellular uptake as detected by fluorescence microscopy and flow cytometry. This study provide theoretical and practical guides for the further application of curcumin nanoliposomes.